Elucidating the anti-oxidant and anti-inflammatory potentials of Triticum aestivum against ulcerative colitis: An in vivo and in silico study - Adebayo-Gege Grace; Maryam Abdullahi Usman; Michael Okwute Ochayi; Moses Dele Adams; Haruna Dan'azumi Umar; Chijioke Dike Obalum; Gabriel Godson Akunna; Ajibola Barth Meraiyebu; Chinedu Onwuchekwa (Elsevier, 2022)
Background: Ulcerative colitis has remained irremediable because of relapse and recurrence despite intake of conventional medicine, although natural products are seen to be a viable alternative. Triticum aestivum is high in antioxidants and anti-inflammatory compounds. Purpose: As a result, its anti-inflammatory activity was elucidated in experimentally induced colitis model to ascertains its anti-inflammatory both invivo and insilico. Study design: The animals (n = 5, 130-200 g) were categorized into four groups and given treatments for three weeks prior to ulcerative colitis induction: I (control), II (acetic acid induced colitis untreated (6% acetic acid), III (acetic acid induced colitis + mesalamine (400 mg/kg), and IV (aqueous extricate of common wheat (200 mg/kg). Methods: The weight changes in the animal's body, the ratio of colon weight and length, the mass of the colon at 8 cm, the relative weight of the colon, the stool scoring, the ulcer score, and the gross morphology of the mucosa layer of the colon were assessed. Spectrophotometry approach was employed to determine the activities of superoxide dismutase and glutathione peroxidase as well as the levels of malondialdehyde, protein, and interleukin-6. A molecular docking investigation of Triticum aestivum compounds against interleukin-6 (IL-6) and cyclooxygenase-2 was then performed (COX-2). Results: When liken with the gastric induced model, the administration of Triticum aestivum elevated the mass of the animals appreciably (p < 0.05) and decreased the weight of the colon at 8 cm, the mass-length ratio, the relative weight of the colon, stool scoring, ulcer score dropped considerably(p < 0.05). The gross morphology showed a significant (p < 0.05) decrease in the hyperemia, inflammation and ulceration after treatment with Triticum aestivum. When liken with the untreated group, MDA and IL-6 levels reduced glaringly (p < 0.05), while GSH and protein levels rose substantively (p < 0.05) after treatment with Triticum aestivum. With various docking outputs, Triticum aestivum compounds interacted with COX-2 and IL-6. Quercetin, protocatechuic acid 4-glucoside, and tricin were the most potent inhibitors of COX-2, whereas stachyose, allantoin, and tetrakis(2-benzimidazolylmethyl)-2‑hydroxy-1,3-diamino propane were the most effective inhibitors of IL-6. These chemicals interacted with key amino acid residues in these molecules' binding sites. Conclusion: The anti-oxidant and anti-inflammatory action of Triticum aestivum reported in this investigation suggest Triticum aestivum plant as a natural replacement and prospective source of a novel ulcerative colitis medication.